2018
DOI: 10.31989/ffhd.v8i7.527
|View full text |Cite
|
Sign up to set email alerts
|

Daily consumption of monoglucosyl-rutin prevents high-fat diet-induced obesity by suppressing gastric inhibitory polypeptide secretion in mice

Abstract: Citation: Yokoyama D., Tanaka W., Hashizune Y., Tandia M., Sakono M., Shimoi K., Sakakibara H. Daily consumption of monoglucosyl-rutin prevents high-fat diet-induced obesity by suppressing gastric inhibitory polypeptide secretion in mice. ABSTRACTBackground: Alpha monoglucosyl-rutin (4 G -α-D-glucopyranosyl rutin, αMR) has been shown to stimulate antioxidant defenses and anti-glycation. We evaluated the effects of αMR on body weight gain in mice. Methods:Male C57BL/6J mice were divided into four groups: Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…(2018) found that MR intake suppressed the increase of GIP caused by a high‐fat diet. They also considered that the suppression of weight gain via MR intake was related to GIP (Yokoyama et al., 2018). Therefore, it is presumed that the reduction in the AVF area confirmed in this study was related to an increase in energy consumption through activation of brown adipocytes and suppression of adipocyte energy accumulation due to the suppression of GIP hypersecretion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2018) found that MR intake suppressed the increase of GIP caused by a high‐fat diet. They also considered that the suppression of weight gain via MR intake was related to GIP (Yokoyama et al., 2018). Therefore, it is presumed that the reduction in the AVF area confirmed in this study was related to an increase in energy consumption through activation of brown adipocytes and suppression of adipocyte energy accumulation due to the suppression of GIP hypersecretion.…”
Section: Resultsmentioning
confidence: 99%
“…In a study using mice, Yokoyama et al. (2018) found that MR intake suppressed the increase of GIP caused by a high‐fat diet. They also considered that the suppression of weight gain via MR intake was related to GIP (Yokoyama et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent models of obesity are frequently studied. The body mass of experimental rodents consuming ad libitum a high-energy diet, such as a high-fat diet, increases much faster than those of rodents consuming a low-energy diet [5].…”
Section: Discussionmentioning
confidence: 98%
“…The use of such diet-induced obesity models has led to the identification of many substances, such as resveratrol, capsaicin and quercetin glycosides, which can protect against excess body mass gain, and therefore obesity [5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%